Relación entre las enfermedades más frecuentes y el rendimiento académico de los estudiantes de la Universidad Nacional José María Arguedas - Salazar Palomino, Sandra (2019)
The present research shows results as how the many sickness affect to the students of José María Arguedas, University of Andahuaylas. How it can influence in their academic performance. The more frequent sickness that the students suffer are: tonsolitis, anemia, bronchitis, cefalea, bruise, skiness, pharyngeal, pharyngeal-tonsilitis, gastritis. G.E.C.A, I.T.U, cold, sinuosity, about all of them, which has the highest percent belonged to the pharyngeal, with 24,2%, the gastritis has 18,7%. According their rating average to the year 2009. According the analyzed sample, these are oscillated between 10 and 15. Being with the most frequency the reting 12. Matching the rating average with the sickness, we can observ that the lowest rate average belongs to the students who had bronchitis, with rating average of 9.14, watching besides that the rating average with each sickness, it doesn`t get to the rating of 13, which it is an indicator at low academic performance. According the multiple analysis of line regression, using as an independent variable the prost frequent sickness (2 cases), the results we deduce that if it exists correlation but in a low level, according the pear son analysis, the bronchitis (99% truth) and the bruise (95% truth), they get an inverse correlation highly meaningful with the rating average gotten. Being the bronchitis as the sickness which bring about the lowest rating average during the academic semester, which the student who has bronchitis is one of them to not be advanced.